1
$\begingroup$

A map $T$ is affine if $T(\sum_{i=1}^n\lambda_i x_i) = \sum_{i=1}^n \lambda_i T(x_i)$ whenever $\sum_{i=1}^n \lambda_i = 1$. I can see that every affine map can be expressed in the form $T(x) = Ax + T(0)$ for some matrix $A$. My course notes state that this matrix can be expressed as $A = (T(e_1), T(e_2), \ldots, T(e_n))$; i.e. the $i$th column of the matrix is $T(e_i)$.

My confusion arises from this definition of $A$. Clearly $Ae_i = T(e_i)$ for all $i$, so we have $T(0) = T(x) - Ax = T(e_1) - Ae_1 = 0$, when clearly not all affine maps map the origin to itself (which is why they are affine and not linear!). Are my notes mistaken about the composition of matrix $A$, or am I missing something obvious?

$\endgroup$
3
$\begingroup$

You are right. $A = (T(e_1), T(e_2), \ldots, T(e_n))$ is true only for linear maps. For an affine map it should be $$ A = (T(e_1)-T(0), T(e_2)-T(0), \ldots, T(e_n)-T(0)). $$ P.S. Basically, the idea is to notice that the map $L(x)=T(x)-T(0)$ is linear and apply the standard matrix construction to it.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.